Avaliação do coeficiente de atrito e caracterização microscópica de uma liga com memória de forma ni-ti - Araújo, André Luiz Silva de (Universidade Federal Rural do Semi-Árido, 2018)
Nickel and Titanium alloys, Nitinol, have shape memory characteristics and superlasticity. If its properties of biocompatibility, biofunctionality due to austenitative-martensite phase transformations, these properties are supported by the properties of the shape memory. Therefore, the Nitinol alloys favor a last application, among them the research allied to applications in engineering. At this juncture, the study of wear, microstructural characteristics and microhardness are important when it is a built tool and, therefore, for a good application. However, there are several sources for the study of the tribological behavior of LMF Ni-Ti. Therefore, this work aims to characterize the friction coefficient with a temperature variation, a microstructure and a microhardness of a Ni-Ti memory alloy by means of a first application with a metallography test (cutting, inlaying, sanding , polishing, etching, microscopy), Vickers microhardness test (microdurometer) and the second stage with tribology (tribometer) tests. Based on the results obtained, a qualitative analysis of the LMF Ni-Ti sample data can be made. It can be verified that the results of optical microscopy showed the characteristics of a martensite, the values of microhardness were convergent, since the results of the coefficient of friction were altered with the increase of the temperature, in general the coefficient of friction remained between the range from 1.4 to 2.0 and close to a test at 60 ºC.
Monografia
Keywords: Ligas com Memória de Forma; Ligas de Ni-Ti; Tribologia; Microdureza; ENGENHARIAS::ENGENHARIA MECANICA